Telaah Nilai Kepastian dan Keadilan pada Regulasi Mahar dalam Pembangunan Hukum Keluarga - Murdiana, Elfa; Zulaikha, Siti; Mahmudah, Nurul (Tapis: Jurnal Penelitian Ilmiah, 2021)
Explicitly, a dowry is not found in the legal protection of marriage, but normatively it is read firmly in Chapter V articles 30 to 38 of the Compilation of Islamic Law. In Article 2 Paragraph 1 of Law No. 1 of 1974 concerning Marriage states that "Marriage is legal, if it is carried out according to the laws of each religion and belief". The explanation of the article emphasizes that there is no marriage if it is not carried out according to religion and belief in accordance with the 1945 Constitution, in which a marriage will be declared valid if a dowry has been paid in it. This study will describe the dynamics of dowry in the meaning of religion and culture associated with several regulations carried out through a policy and cultural approach. The data collection techniques used were interviews and an inventory of policies on marriage and dowry which were described inductively to find the dowry formulation as part of the Ius Constituendum on Marriage Law in Indonesia. The indecisiveness of the Marriage Law as a Formal Gezet in the implementation of marriage is indicated as a factor causing the various meanings and implementation of the dowry, like the pillars and conditions of marriage. So that the essence of the dowry as the actualization of the role of women to express their rights in marriage is still injured because the dowry is actualized as a bargaining transaction between the two families of the groom and the bride. So that the high dowry actually makes women the object of transactions that reduce their rights in the implementation of marriage. Efforts to change the legal umbrella of marriage in Indonesia should be carried out for the sake of certainty and justice of marriage law for all Indonesian people, especially in the concept of dowry payments so that it can be used as the basis for the Compilation of Islamic Law in Indonesia. It is hoped that the dowry regulation can be clearly broken down in creating legal certainty and justice.